2003
DOI: 10.1128/jvi.77.5.3148-3156.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Quail in the Interspecies Transmission of H9 Influenza A Viruses: Molecular Changes on HA That Correspond to Adaptation from Ducks to Chickens

Abstract: H9 influenza viruses have become endemic in land-based domestic poultry in Asia and have sporadically crossed to pigs and humans. To understand the molecular determinants of their adaptation to land-based birds, we tested the replication and transmission of several 1970s duck H9 viruses in chickens and quail. Quail were more susceptible than chickens to these viruses, and generation of recombinant H9 viruses by reverse genetics showed that changes in the HA gene are sufficient to initiate efficient replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
148
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(164 citation statements)
references
References 34 publications
14
148
1
Order By: Relevance
“…The quantity of adaptive mutations necessary for an avian virus of a particular subtype to cross the species barrier is unknown. Our results are consistent with the notion that changes on the surface genes alone are insufficient for the transmission of avian influenza viruses in chickens (19,26,34,35). It should also be noted that the changes that occurred during adaptation in quail were maintained in 7 passages of the virus in chickens and were found to be necessary for transmission.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The quantity of adaptive mutations necessary for an avian virus of a particular subtype to cross the species barrier is unknown. Our results are consistent with the notion that changes on the surface genes alone are insufficient for the transmission of avian influenza viruses in chickens (19,26,34,35). It should also be noted that the changes that occurred during adaptation in quail were maintained in 7 passages of the virus in chickens and were found to be necessary for transmission.…”
Section: Discussionsupporting
confidence: 81%
“…Japanese quail are typically more susceptible to aquatic influenza viruses than other terrestrial poultry. These viruses establish infection in the respiratory tract, and shedding occurs via aerosol (2,19,26,34,38,43). Quail have been implicated in the transmission of avian influenza viruses, such as H5N1 and H9N2 viruses, which have crossed the species barrier to infect humans (9,14,15,22,28).…”
mentioning
confidence: 99%
“…Previous AIV transmission studies in quail have had mixed results. Perez et al (2003), in their studies of Asian duck H9 AIV, did not observe transmission from inoculated to susceptible quail through either direct or indirect contact 5 to 7 days post inoculation, but did observe transmission of an Asian quail H9 AIV to quail and chickens with faecal contact. It is possible that transmission of the AIV subtypes studied by Perez et al would have been observed if the experiment were extended beyond 7 days post inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, pheasants can serve as a "carrier" of influenza A viruses because of their continuous asymptomatic infection (20). On the other hand, previous studies indicate that quails play a significant role in the interspecies transmission of influenza virus from ducks to chickens (21). Domestic poultry such as quail and chicken possess α2, 3 and α2, 6 sialic acid receptors that may help passage of avian influenza viruses from bird species (such as ducks with only α2, 3 sialic acid receptor) to human with predominant α2, 6 sialic acid receptors (22,23).…”
Section: Discussionmentioning
confidence: 99%